2020
DOI: 10.1177/2515841420903929
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intravitreal injection of aflibercept on blood coagulation parameters in patients with age-related macular degeneration

Abstract: Purpose: Treatment with intravitreal injections of anti-vascular endothelial growth factor agents has been associated with an increased risk of arterial thromboembolic events. The aim of the present pilot study was to assess the effect of a single intravitreal injection of aflibercept on coagulation. Methods: Treatment-naïve patients with age-related macular degeneration (n = 47), who were scheduled to undergo treatment with intravitreal injections of aflibercept, were enrolled. None of the included patients r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…To date, four studies assessing the influence of intravitreal injections of anti-VEGF agents on the coagulation parameters have been published [ 9 , 13 , 20 , 21 ]. In patients with proliferative diabetic retinopathy (PDR), the effect of IVB on prothrombin time was evaluated [ 13 ], while another study evaluated clotting time, serum fibrinogen level, and blood viscosity in patients with CNV treated with IVR [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To date, four studies assessing the influence of intravitreal injections of anti-VEGF agents on the coagulation parameters have been published [ 9 , 13 , 20 , 21 ]. In patients with proliferative diabetic retinopathy (PDR), the effect of IVB on prothrombin time was evaluated [ 13 ], while another study evaluated clotting time, serum fibrinogen level, and blood viscosity in patients with CNV treated with IVR [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the third study, changes in APTT and PT were measured in patients with nAMD who received IVA [ 20 ]. Georgakopoulos et al assessed the effect of IVA on platelet count, PT, APTT, and fibrinogen, D-dimer, and protein C and S levels in the serum of patients with AMD [ 21 ]. Altinkaynak et al revealed a decrease in APTT and PT values both one month after the first IVA injection and one month after the second injection in patients with nAMD; however, in both measurement points the results were not statistically significant [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We hypothesize that the causes may be multifaceted including specific drug related blood chemistry changes and patients’ health conditions. A few studies have looked into the blood coagulation parameters following intravitreal injection of bevacizumab 14 or aflibercept 9 , 10 or ranibizumab 12 . In contrast, so far there is no similar report following intravitreal conbercept.…”
Section: Discussionmentioning
confidence: 99%